Innovational and investment security of modern development and assessment of the result of the mechanism of its supply on the state and regional levels - Komelina, Olha; Zaiats, Tatyana; Rakhmetulina, Zhibek; Komelina, Anna (International Journal of Engineering and Technology, 2018)
Purpose of the article is to analyze the concept of production competitiveness and develop framework of cost management. A variety of cost management techniques requires the identification of their relationship with the requirements of operations management. Identified seven key concepts of operations management, analyzed their essence, information requirements. Systematized cost management techniques accordance with modern concepts of operations management such as: standart-costing, break-even analysis, direct-costing, life-cycle costing, target costing, value analysis, functional analysis, activity-based costing, sensitivity analysis, JIT-costing, kaizen costing, activity-based cost management, value-chain analysis. The aim of the article is the establishment relevance of costing methods with the key concepts of operations management companies.The article deals with the problems of formation of innovational and investment security and its influence on the economic development of Ukraine and the macro-environment favorable for business development. For this purpose the integral indicator of Ukraine’s economic security and its components are calculated: investment-innovation, production, demographic, energy, foreign economic, macroeconomic, food, social, and financial.Significant deterioration in the macroeconomic environment in Ukraine during 2014 – 2017 yrs. was accompanied by a decline in its competitive position at the global level and the ability to compete with other major investment-friendly countries for foreign investors in the world. The main attention is paid to the identification of modern factors of influence that promote or hinder the development of innovation and investment activities. There are revealed the reasons for the formation of negative trends in the development of innovation activity in the system of ensuring economic security of the state, which is amplified by the low level of its investment attractiveness as a whole, as well as the limited investment opportunities for further development of the country.The conceptual model of the mechanism for providing innovative and investment security at the state and regional levels, aimed at technological modernization of the economy, is proposed. It is argued that the effectiveness of this mechanism is ensured through the commercialization of the results of innovation activities. The approach to assess the effectiveness of the mechanism of commercialization of innovations and their impact on the formation of innovation and investment security of development in the regions of Ukraine, which takes into account the intensity of the production of new knowledge; the speed of transforming new knowledge into specific technologies, products, services; the effectiveness of innovation and investment activity; the level of perception of changes or the readiness of enterprises for the implementation of innovative technologies; network technological readiness of the region, etc. This approach is important from the point of view of implementing of the European methodology of a reasonable specialization of the regions of the country.
Keywords: economic security; innovational and investment security; effectiveness of the mechanism of innovations commercialization; country; region; smart specialization.